Volumetric strain behaviour and self-healing of large scale engineered cementitious composite and normal concrete panels under natural conditions. (15th November 2021) - Hooshmand, Ahmad; Kianoush, Reza; Siad, Hocine; Lachemi, Mohamed; Booya, Emad; Moslemi, Mehdi
Highlights: Volumetric strain cracking and self-healing were considered under natural conditions. Large scale ECC and NC panels were restrained to represent a segment of LCS. Fly ash and slag highly influenced the ability of ECC to be used safely in LCS. W/D cycles helped on the self-healing of ECC and influenced negatively the cracking of concretes. The self-healing products in ECC/FF resisted better the F/T cycles than ECC/SL and NC. Abstract: The application of engineered cementitious composite (ECC) in liquid containing structures (LCS) may help to improve the cracking performance of these structures. This study investigates the hydration temperature, shrinkage, cracking and self-healing behaviors of 10 m length ECC and normal concrete (NC) panels under real field conditions of volumetric strains. The restrained panels of NC and ECCs, with different compositions of fly ash (ECC/FF) and slag (ECC/SL), were designed to represent a segment of LCS and were cast and monitored on site for seven months under natural temperature changes of wet/dry and freeze/thaw cycles. A detailed microstructural analysis was completed on full depth drilled cores to explore the self-healing efficiency of different crack layers. At 28 days, only ECC/SL exceeded the ACI 224R limit for crack width of concretes to be used safely in LCS. However, at longer ages, unlike ECC/FF and ECC/SL panels which showed significant healing of their volumetric strain cracks, the NC panel experienced a sharp increase in crack widths up to seven months of monitoring. Different concentrations of CaCO3 and C-S-H/CH products were characterized at the top, core and bottom layers of crack lines, confirming higher self-healing performance of the volumetric strain cracking in ECC/FF compared to ECC/SL and NC segments.